Evolutionary analysis of tomato Sw-5 resistance-breaking isolates of Tomato spotted wilt virus - Lopez, Carmelo; Aramburu, Jose; Galipienso, Luis; Soler, Salvador; Nuez, Fernando; Rubio, Luis (2017)
Tomato spotted wilt virus (TSWV) causes severe economic losses in many crops worldwide and often overcomes resistant cultivars used for disease control. Comparison of nucleotide and amino acid sequences suggested that tomato resistance conferred by the gene Sw-5 can be overcome by the amino acid substitution C to Y at position 118 (C118Y) or T120N in the TSWV movement protein, NSm. Phylogenetic analysis revealed that substitution C118Y has occurred independently three times in the studied isolates by convergent evolution, whereas the substitution T120N was a unique event. Analysis of rates of non-synonymous and synonymous changes at individual codons showed that substitution C118Y was positively selected.